The image of a political entity in the regional dimension: The specifics of formation and peculiarities of perception by public opinion - Alexander V. Tolochko; Sergey S. Fomenko (RUDN Journal of Public Administration)
The research identifies key problems in the field of correcting and maintaining the image of a political subject in the mass media and deepens the differentiation of concepts from the sphere of political image. Practical recommendations are offered for optimizing strategies and technologies for improving the image characteristics of a political subject using PR communications, visual and verbal components available in the arsenal of practical politicians, which are offered to them by moderators of political image-making processes at the regional level. The results of the study can be used to effectively build the image of a regional politician and develop an image strategy and tactics within the framework of electoral cycles. The factual material, theoretical provisions and conclusions proposed by the authors of the research can be used in teaching elective courses related to political science issues. The results of the study can also be useful in the cultural and educational activities of participants in election campaigns and those interested in the regional political process in modern Russia.